On the synonymy of Caristius groenlandicus Jensen and Pteraclis fasciatus Borodin (Pisces: Caristiidae) - Britz, Ralf; Hartel, Karsten E. (Zootaxa, 2012)
Manefishes of the family Caristiidae are rare meso-bathypelagic oceanic fishes with numerous problems regarding theirspecies-level taxonomy. We revisit Hartel and Triant’s assertion (Copeia, 1998, 746) that Pteraclis fasciatus Borodin andCaristius groenlandicus Jensen are synonyms. We found additional support for this idea in the modification of theventral unbranched caudal-fin rays. We conclude that the names are synonyms and that fasciatus has priority over groenlandicus because the former is the older name.